Asynchrony of primary tumor and mediastinal lymph nodes response after neoadjuvant immunotherapy plus chemotherapy in a patient with stage IIIA non–small-cell lung cancer: a case report. Issue 1 (January 2022) - Liu, Yunpeng; Gao, Zhiru; Zhang, Chengbin; Liu, Xing; Liu, Zihao; Lin, Xingyu; Qian, Benxin; Jin, Fukang; Shao, Guoguang; Yang, Zhiguang
Abstract : With the rapid development of immunotherapy, the efficacy and feasibility of neoadjuvant immunotherapy for early resectable non–small-cell lung cancer (NSCLC) has been demonstrated. However, there are still difficulties and controversies in evaluating the efficacy of neoadjuvant immunotherapy. In our report, we described a 43-year-old female patient who was diagnosed with stage IIIA (cT1N2M0) pulmonary adenocarcinoma. After two cycles of neoadjuvant immunotherapy (sintilimab) combined with chemotherapy, according to imaging evaluation, the efficacy of the primary lesion was evaluated as stable disease and the mediastinal lymph nodes were evaluated as partial response. However, the postoperative pathological evaluation showed the primary lesion was pathological complete response and the mediastinal lymph nodes were major pathological response. This indicated that neoadjuvant chemo-immunotherapy was effective for both primary and mediastinal lymph nodes, but regression of the lesions was not synchronous. This study provided a complete process of neoadjuvant treatment, illustrating the effectiveness and safety of neoadjuvant chemo-immunotherapy to a certain extent. It is also suggested that the evaluation of neoadjuvant immunotherapy should be combined with imaging and pathology, and the primary tumor and lymph nodes should be evaluated, respectively.